THE THREE OF DYES TO SEE METACROMATIC GRANULA - Sudibya, Akhmad (Universitas Wijaya Kusuma Surabaya, 2012)
There are two stains in addition to Â Neisserâs Stain to detect metachromatic granules. The two stains are Albertâs Diphtheria Stain and Loefflerâs Alkalin Methylene Blue Stain for Metachromatic Granules. They should be taught to medical students.Â